2008
DOI: 10.1089/clo.2007.0075
|View full text |Cite
|
Sign up to set email alerts
|

Serum-Free Differentiation of Murine Embryonic Stem Cells into Alveolar Type II Epithelial Cells

Abstract: Alveolar type II (AT2) epithelial cells have important functions including the production of surfactant and regeneration of lost alveolar type I epithelial cells. The ability of in vitro production of AT2 cells would offer new therapeutic options in treating pulmonary injuries and disorders including genetically based surfactant deficiencies. Aiming at the generation of AT2-like cells, the differentiation of murine embryonic stem cells (mESCs) toward mesendodermal progenitors (MEPs) was optimized using a "Brac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 39 publications
2
31
0
Order By: Relevance
“…NKX2-1 can be induced in mouse (m) or human embryonic stem cell (hESC) in vitro [10][11][12][13][14][15][16]. Some studies have suggested that Activin-A [12,13] positively influences the differentiation ability of m/hESC towards NKX2-1 expressing pulmonary epithelium, whereas other studies suggest that pulmonary epithelium specification from the ventral foregut requires dual inactivation of BMP4/transforming growth factor (TGF) beta.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…NKX2-1 can be induced in mouse (m) or human embryonic stem cell (hESC) in vitro [10][11][12][13][14][15][16]. Some studies have suggested that Activin-A [12,13] positively influences the differentiation ability of m/hESC towards NKX2-1 expressing pulmonary epithelium, whereas other studies suggest that pulmonary epithelium specification from the ventral foregut requires dual inactivation of BMP4/transforming growth factor (TGF) beta.…”
mentioning
confidence: 99%
“…Some studies have suggested that Activin-A [12,13] positively influences the differentiation ability of m/hESC towards NKX2-1 expressing pulmonary epithelium, whereas other studies suggest that pulmonary epithelium specification from the ventral foregut requires dual inactivation of BMP4/transforming growth factor (TGF) beta. Some but not all studies have demonstrated that high concentrations of FGF2 increase NKX2-1 expression in differentiating hESC [9,10,15].…”
mentioning
confidence: 99%
“…However, the lung epithelial cells derived by this method had a gene expression profile resembling that of the lung committed precursor (SPC + Ttf1 + ) found in foregut endoderm, rather than mature alveolar epithelium. While trying to optimize serum free conditions for lung epithelial cell differentiation, Winkler et al (2008) observed in the presence of serum relatively high expression levels of surfactant proteins A, B, C and D, CCSP and aquaporin 5, suggesting that epithelial cells expressing the markers for mature type II alveolar epithelium cells could be generated in serum-containing conditions. Surprisingly, a late treatment with ActivinA following serum activation resulted in significantly higher expression levels of SPC compared to an early induction with ActivinA.…”
Section: Differentiation Of Es Cells Into Lung Epithelial Cellsmentioning
confidence: 99%
“…It has been shown that four factors present in ESC are sufficient to re-induce a pluripotent state in somatic cells. The reprogramming of somatic cells to a pluripotent state can be achieved by simple retroviral overexpression of specific transcription factors, resulting in induced pluripotent stem (iPS) cells that are almost indistinguishable from ESC (Okita K 2007;Narazaki G 2008;Winkler ME 2008). Transduction of fibroblasts with only four transcription factors, Oct4, Sox2, cMyc and Klf4, could dedifferentiate the fibroblasts to cells with almost all features of ESC.…”
Section: Induced Pluripotent Stem Cellsmentioning
confidence: 99%